The Influence of Teacher Motivation and Skills on Performance through Leadership Intervening Variables - Soim Soim; Nik Haryanti; Ali Mufron; Nita Agustina Nurlaila Eka Erfiana (Al-Hayat: Journal of Islamic Education, 2022)
This study aims to determine the effect of teacher motivation and skills on performance through leadership as an Intervening Variable in MA Ma'arif Udanawu Blitar. This type of research is quantitative research. The population used in this study were all teachers, namely 69. Sampling in this study was saturated sampling, namely the sampling technique when all members of the population are used as samples. Data collection techniques using a questionnaire. Data analysis methods using path analysis with the IBM SPSS statistical 22 programs. The results showed that there was a significant influence of teacher motivation and skills on performance through leadership. The higher the teacher's motivation and skills, the higher the performance and leadership. There is an indirect effect of work motivation on teacher performance through leadership as an intervening variable at MA Ma'arif Udanawu Blitar, as evidenced by the results of the sobel test, which is greater than t-table means there is a mediating effect. Leadership can be a mediating variable between work motivation on teacher performance. Work skills influence teacher performance through leadership as an intervening variable at MA Ma'arif Udanawu Blitar, as evidenced by the results of the Sobel test, which is greater than t-table, which means there is a mediating influence. So, leadership can mediate between work skills and teacher performance.